Development Aid Confronts Politics: The Almost Revolution - Carothers, Thomas; Gramont, Diane (EDS Publications Ltd., 2013)
A new lens on development is changing the world of international aid. The overdue recognition that development in all sectors is an inherent ly political process is driving aid providers to try to learn how to t hink and act politically. Major donors are pursuing explicitly politic al goals alongside their traditional socioeconomic aims and introducin g more politically informed methods throughout their work. Yet these c hanges face an array of external and internal obstacles, from heighten ed sensitivity on the part of many aid-receiving governments about for eign political interventionism to inflexible aid delivery mechanisms a nd entrenched technocratic preferences within many aid organizations. This pathbreaking book assesses the progress and pitfalls of the attem pted politics revolution in development aid and charts a constructive way forward.